The prevalence of precocious puberty among children in Qufu City, Shandong Province, China, a population-based study - Zhang, Yawen; Ni, Jianmin; Zhang, Lei; Yu, Tingting; Li, Xiaoqing; Xue, Peng; Liu, Yifan; Gao, Bo; Xue, Xinwen; Kong, Huijun; Liu, Shijian (Frontiers in Endocrinology, 2022)
Objective: We sought to investigate the prevalence of precocious puberty in children aged 6–10 years in Qufu City, Shandong Province, China. Methods: A total of 5,169 primary school students from grades 1–3 were recruited by population-based multi-stage stratified cluster random sampling. Professional pediatricians conducted physical examinations in October 2020. Precocious puberty is defined as the onset of secondary sexual characteristics in boys aged < 9 years or girls < 8 years or menstruation in girls < 10 years old. Tanner staging was used to record the development of breast and pubic hair in girls and testicular volume and pubic hair in boys. According to the standards of the International Obesity Task Force, we diagnosed overweight, obesity, or severe obesity. In obese girls, a combination of palpation and ultrasound was used to evaluate breast development. The difference was tested by chi-squared test, and all data were statistically analyzed using IBM SPSS version 25.0 (IBM Corporation, Armonk, NY, USA). Results: The unadjusted and adjusted prevalence rates of precocious puberty were 5.01% (11.53% for girls and 1.41% for boys) and 6.29% (14.23% for girls and 1.54% for boys), respectively. The prevalence of precocious puberty in urban (5.34%) dwellers was much higher than that in suburban residents (2.36%, P < 0.05). The prevalence of precocious puberty in the overweight (21.43% for girls and 1.97% for boys), obesity (35.48% for girls and 4.6% for boys), and severe obesity (32.35% for girls and 3.38% for boys) groups were higher than that in the normal weight group (4% for girls and 0.54% for boys, P < 0.05). Conclusion: The prevalence of precocious puberty is high, and overweight and obesity are related to precocious puberty in Qufu, Shandong Province, China.